Clean and Healthy Lifestyle Education (PHBS) as a Strategy to Prevent Toddlers Diarrhea at Posyandu Mawar Kemayoran - Kushargina, Rosyanne; Zulfa, Aribah; Azkiya, Dinda Maulida; Fayza, Lakisha; Hendriani, Putri Faidah; Nadiyatuzahrah, Qathrah (Jurnal Abmas Negeri (JAGRI), 2025)
Diarrhea is an infectious disease that is often experienced by toddlers. Diarrhea among toddlers needs to be treated promptly. Toddlers who experience diarrhea are susceptible to nutritional problems, especially weight loss. Monitoring the nutritional status and health of toddlers is very important and can be monitored through the implementation of integrated health service posts (Posyandu). Through Posyandu, education for diarrhea prevention and treatment efforts for parents of toddlers can also be provided. This activity aimed to provide education on diarrhea prevention and treatment efforts to parents of toddlers. Educational materials are provided through lecture and discussion methods regarding the definition, signs, symptoms, management, and prevention of diarrhea through the implementation of Clean and Healthy Living Behaviors (PHBS). Participants in the activity were 13 mothers of toddlers in the work area of ​​Posyandu Mawar, RW 06 Kemayoran, Central Jakarta. Pre- and post-tests were conducted as a form of monitoring and evaluation of the achievement of this activity. The success of the activity is seen from the increase in pre- and post-test scores. As many as 77% of participants with post-test scores remained/increased from the pre-test score, which indicated that there has been an increase in participants' knowledge of the educational material that has been provided. It is hoped that this activity can continue to be carried out to further strengthen knowledge and motivate participants to implement diarrhea prevention and treatment efforts in their daily lives and improve toddler health.